2011
DOI: 10.1038/oby.2011.57
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Food Reward: Delay Discounting, Food Reward Sensitivity, and Palatable Food Intake in Overweight and Obese Women

Abstract: Overeating is believed to result when the appetitive motivation to consume palatable food exceeds an individual’s capacity for inhibitory control of eating. This hypothesis was supported in recent studies involving predominantly normal weight women, but has not been tested in obese populations. The current study tested the interaction between food reward sensitivity and inhibitory control in predicting palatable food intake among energy-replete overweight and obese women (N=62). Sensitivity to palatable food r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
187
5
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(215 citation statements)
references
References 40 publications
19
187
5
4
Order By: Relevance
“…In addition, foodspecific inhibitory control was measured, rather than a general inability to inhibit responses (Houben & Wiers, 2009;Peeters et al, 2012). Food-specific inhibitory control has been argued to be particularly important with regard to achieving a more detailed understanding of the mechanisms which may be associated with unhealthy eating (Appelhans, et al, 2011;. In support, neuroimaging research has shown that brain regions associated with motivation and disinhibition are activated in obese people in response to unhealthy food images (Carnell, Gibson, Benson, Ochner, & Geliebter, 2012).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, foodspecific inhibitory control was measured, rather than a general inability to inhibit responses (Houben & Wiers, 2009;Peeters et al, 2012). Food-specific inhibitory control has been argued to be particularly important with regard to achieving a more detailed understanding of the mechanisms which may be associated with unhealthy eating (Appelhans, et al, 2011;. In support, neuroimaging research has shown that brain regions associated with motivation and disinhibition are activated in obese people in response to unhealthy food images (Carnell, Gibson, Benson, Ochner, & Geliebter, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…Several studies have also demonstrated that poor inhibitory control is associated with increased food intake during a laboratory taste test in both healthy weight (Guerrieri, Nederkoorn, & Jansen, 2007) and overweight or obese women (Appelhans et al, 2011). In addition, poor inhibitory control predicted an increase in weight (BMI) over a one year period in a sample of healthy weight women (Nederkoorn, Houben, Hofmann, Roefs & Jansen, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The rewarding value, evaluated in terms of reinforcing value, of palatable foods is higher than that of bland foods [15][16][17][18]. However, not all people indulge in highly palatable or reinforcing foods such as energy-dense snacks and SSBs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, obese women show steeper discounting of delayed rewards than normal weight women [52], and greater delay discounting has been associated with higher intake of palatable food among lean, overweight, and obese subjects who are most sensitive to the rewarding properties of food [53,54]. It has been hypothesized that a greater predisposition for delay discounting would likely manifest as heightened sensitivity to the immediate reward from palatable food and decreased valuation of the longterm rewards associated with a healthy diet and weight maintenance, which in combination would contribute to obesity [55,56].…”
Section: Introductionmentioning
confidence: 99%